(untitled) (Journal of the Bangladesh Association of Young Researchers, 2014)
Attention Readers and Researchers "PDF version of this article has been modified two to three times due to problems with one figure and with missing words in the title. The final version of the PDF was last updated on September 27, 2014. We apologise for the inconvenience this might cause." Abstract The role of emotion in memory recollection has been an arguable issue for a decade. Episodic memory is very triggering in our day to day life and so as our affective states. Present study was conducted to see whether positive, negative and neutral emotional states (affective states) have any effect in recollecting emotion congruent or incongruent episodic memory. Words of positive, negative, or neutral were presented to the participants either in positive, negative, or neutral mood and immediate recall was used in this present experiment. It was hypothesized that congruent mood would enhance better episodic memory recollection than incongruent mood. A total of 36 adult healthy participants were selected for this experiment following an incidental sampling techniques and they were divided into two contrasting groups namely, congruent and incongruent following purely on the basis of chance. Phases of stimulus presentations were counterbalanced. Different images were used to manipulate affective states of the respondents, and different positive (18 words), negative (18 words) and neutral (18 words) words were used as stimulus. Results were analyzed using paired t test. Results revealed that negative mood enhance negative word retrieval (t = 2.159, p <0.05) but not positive words. Findings were discussed in the light of current theories of episodic memory recollection. DOI: http://dx.doi.org/10.3329/jbayr.v2i1.20536 Journal of the Bangladesh Association of Young Researchers (JBAYR): Vol.2(1), 2012 & 2013: 1-8